Alagamentos e inundações na bacia do Ribeirão Pirapitinga em Catalão - GO - (:unkn) unknown (Universidade Federal de Goiás, 2020)
Urban planning in many Brazilian cities did not occur at the same pace of growth, or what occurred in a disorderly occupation of urban physical space, readjusting environmental damage to water courses, as well as problems related to drainage, who in Brazilian cities have proportions each a times larger, as does large studies that analyze this problem. Thus, this work aims to assess the impact of urbanization on a hydrological performance in the Ribeirão Pirapitinga Basin, seeking to analyze the phenomenon resulting from urbanization, to define the floods and floods in the city of Catalão. The methodological procedures adopted to carry out this theoretical research, the realization of a discussion about how urbanization took place as well as the adoption of the hydrographic basin as a planning unit and as implications for the urban drainage of the city of Catalão. Also use documentary research to analyze population data and survey flooding and flooding in the city of Catalão.
Flood and flooding in the Ribeirão Pirapitinga in Catalão - GO
Keywords: Planejamento urbano; Alagamentos; Inundações; Catalão; Urban planning; Floods; Catalão; Inundation; CIENCIAS HUMANAS::GEOGRAFIA